Pre feasibility of cogeneration in a hotel in Bangladesh - Sarkar, M. A. R.; Obaidullah, M. (Nepalese Journal of Engineering, 2005)
Pre feasibility of cogeneration in a hotel in Bangladesh was carried out. Information on steam and electricity consumption in a hotel was collected through site visits and surveys via questionnaire. Historical energy consumption data shows that the power to heat ratio of the plant was 0.35. For average power to heat ratio of 0.35, three types of the prime movers i.e. steam turbine, reciprocating engine and gas turbine cogeneration system was considered. From the sensitivity analysis the potential cogeneration alternatives of the hotel, the reciprocating engine power match option meeting power requirement of 525 kW to be the most suitable co-generation system. It represents an initial investment of 0.034 billion Taka (1 US = Tk 58) and leads to an internal rate of return of 41.8%. Keywords: cogeneration, sensitivity analysis,energy class. Nepalese Journal of Engineering Vol.1(1) 2005 pp. 76-79